"\\mathbf{Given:\\;(y-(cos\\;x)^2)dx+cos\\;x\\;dy=0}"
"\\mathbf{We\\;have\\;:\\dfrac{(y-cos^2x)}{cos\\;x}+\\dfrac{dy}{dx}=0}"
"\\implies \\mathbf{\\dfrac{dy}{dx}+\\dfrac{y}{cos\\;x}=cos\\;x}\\\\ \\\\"
"\\therefore\\;\\mathbf{This\\;is\\;in\\;the\\;form\\;of\\;Bernoulli's\\;equation,so\\;-}\\\\ \\\\\n\\mathbf{Integrating\\;factor=I.F.=exp\\left(\\int\\dfrac{1}{cos\\;x}dx\\right)=exp\\left(\\int{sec\\;x}dx\\right)}"
"=\\mathbf{exp(ln|sec\\;x+tan\\;x|)}"
"=|\\mathbf{sec\\;x+tan\\;x}|"
"\\therefore\\mathbf{Solution\\;is-}"
"\\mathbf{y(I.F.)=\\int Q(x)(I.F.)dx+C,\\;(here\\;Q(x)=cos\\;x)}"
"\\mathbf{So,\\;we\\;have\\;solution-}"
"\\mathbf{y(|sec\\;x+tan\\;x|)=\\int cos\\;x(|sec\\;x+tan\\;x|)dx+C}"
"\\implies \\mathbf{y(|sec\\;x+tan\\;x|)=\\int (1+sin\\;x)dx+C}"
"\\implies \\mathbf{y(|sec\\;x+tan\\;x|)= x-cos\\;x+C\\;\\;\\;\\;............Ans.}"
Comments
Leave a comment